The Nile Basin water resources: overview of key research questions pertinent to the Nile Basin initiative - Mohamed, Yasir; Loulseged, Makonnen (International Water Management Institute, 2008)
The Nile Basin Initiative (NBI) is a remarkable achievement towards the cooperative management of the common Nile water resources. Based on a Shared Vision Program and a Subsidiary Action Program, the NBI has numerous ongoing projects on the ground. Research on the Nile water resources has been recognized to be crucial for successful implementation of the NBI projects. Therefore, IWMI and other research centers have worked together with the NBI to identify knowledge gaps pertinent to the Nile water resources. This report presents prioritized research questions, pertinent ongoing research projects and the implementing institutions; and available databases on the Nile.